2018
DOI: 10.1103/physreve.98.043207
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic-electron-driven magnetic reconnection in the laboratory

Abstract: Magnetic reconnection is a fundamental plasma process involving an exchange of magnetic energy to plasma kinetic energy through changes in the magnetic field topology. In many astrophysical plasmas magnetic reconnection plays a key role in the release of large amounts of energy [1], although making direct measurements is challenging in the case of high-energy astrophysical systems such as pulsar wind emissions [2], gamma-ray bursts [4], and jets from active galactic nuclei [5]. Therefore, laboratory studies of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 57 publications
0
30
0
1
Order By: Relevance
“…For our retrieved magnetic fields, this ratio was estimated to be δ/L ≈ 0.14, using the FWHM of the best-fit Gaussian of the width, and defining the length of the region by the intersection point of the two bubbles. This is possibly an underestimate since the L is not FWHM as with δ. Raymond et al observed δ/L ≈ 0.3 using copper K α emission and numerical modeling in a similar regime [31]. It is, however, consistent with fast, collisionless reconnection which predicts rates of 0.1-0.2v A [19].…”
Section: Experimental Datamentioning
confidence: 83%
See 1 more Smart Citation
“…For our retrieved magnetic fields, this ratio was estimated to be δ/L ≈ 0.14, using the FWHM of the best-fit Gaussian of the width, and defining the length of the region by the intersection point of the two bubbles. This is possibly an underestimate since the L is not FWHM as with δ. Raymond et al observed δ/L ≈ 0.3 using copper K α emission and numerical modeling in a similar regime [31]. It is, however, consistent with fast, collisionless reconnection which predicts rates of 0.1-0.2v A [19].…”
Section: Experimental Datamentioning
confidence: 83%
“…The fields have strength of the order 100 MG contained within a thin layer close to the target surface and initially expand at close to the speed of light. Using these "relativistic" intensities to drive magnetic reconnection was recently investigated using copper K α emission and magnetic spectrometers to diagnose the fast electrons [31]. Within the thin, hot plasma surface layer, where the magnetic fields are present, numerical modeling found the conditions to be such that the cold electron magnetization parameter σ cold = B 2 /(µ 0 n e m e c 2 ) > 1.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as the whole setup is micro-scale, the PIC simulations are considerably less expensive than in previous laser-plasma driven MR experiments. 31 Since some processes of interest, such as the particle acceleration, can only be captured by means of fully-kinetic PIC simulations, it is therefore more accessible to guide and interpret future MR experiments via numerical simulations with the proposed scenario. Nevertheless, it is worth noting that despite the small physical size (L ∼ 1 − 10µm), due to the high energy density, in dimensionless variables 48 [L/( β d i ) ∼ 10, where d i is the ion skin depth] the system here is comparable to previous laser-plasma MR experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the previous studies are focused on the non-relativistic limit, it has been reported recently that relativistic MR conditions can be achieved with such a scenario in laboratory environments. 31 In the laser-driven reconnection studies based on the Biermann battery effect, [21][22][23][24][25][26][27][31][32][33] due to the oppositely directed magnetic fields that need to be compressed together by the plasma thermal flows, the ratio of the plasma thermal and magnetic energy, β , is high (β > 1). As a result, the plasma is not magnetically dominated and it is therefore not clear what role MR plays in terms of energy balance.…”
mentioning
confidence: 99%
“…Frontside copper K α images from focal spot separation scans using the OMEGA EP laser. 50 µm horizontal line-outs are superimposed [41] . the coils can be simulated by Radia code [36] .…”
Section: Helmholtz Coils Mr With Long-pulse Lasersmentioning
confidence: 99%